Decoding urbanization trade-offs in Shenzhen, China: a PLUS-InVEST-PLES framework for balancing carbon dynamics, ecological functionality, and land use intensification - Li, Yu; Li, Ruifan; Yu, Hongbing; Yu, Han (Frontiers in Environmental Science, 2025)
Urbanization in coastal megacities leads to trade-offs between development and ecology, degrading carbon sinks and disrupting spatial-functional balance. Current models often fail to integrate land use, carbon dynamics, and ecological zoning. This study created a system that brings together Patch-generating Land Use Simulation (PLUS), Integrated Valuation of Ecosystem Services and Trade-offs (InVEST), and Production-Living-Ecological Space (PLES) to examine how urban growth affects carbon storage and ecological balance in Shenzhen, China. Using GlobeLand30 datasets (2000–2020), land use was simulated under ecological priority scenarios until 2030. Findings revealed that a 50.15% expansion of built-up areas caused a 7.9% decline in carbon stock, with coastal areas hit hardest. Production-Living-Ecological Space coordination improved slightly, but urban areas showed imbalances. A zoning scheme identified 40% built-up land as the threshold for carbon collapse, and the 2010 ecological control line policy reduced carbon loss by 41%. This study offers a replicable model for balancing urban development with ecological resilience.